Meta-Analysis: The Relationship Of Gender And Smoking Habits With The Event Of Hypertension - Armuni Armuni; Bahrul Ilmi; Syamsul Arifin; Husaini Husaini; Meitria Syahadatina Noor (Healthy-Mu Journal, 2021)
Hypertension is a hidden threat because it often occurs without symptoms. The high mortality rate due to hypertension is recorded at 45% according to WHO. Factors that trigger hypertension include age, gender, family history, smoking habits, salt consumption, saturated weak consumption, alcoholic beverages, obesity, lack of physical activity, stress and estrogen disorders. Gender and smoking variables are interesting to study because Indonesia is one of the countries with the largest number of smokers in the world. From WHO data in 2008, Indonesia ranks third after China and India in the ten largest smoking countries. The number of smokers reaches 65 million people. The purpose of this study was to determine the tendency of the relationship between sex and smoking habits on the incidence of hypertension using the meta-analysis method. Article used as datasource from Google Scholar and PUBMED. Of the 299 articles that were screened based on the specified inclusion criteria, 12 articles were used as the database of this study. The results showed that there was a relationship between smoking habits and gender with the incidence of hypertension with the incidence of hypertension was 1.397 with a 95% CI: 1.212-1.611. The combined effect also resulted in a Z value of 4.611 and a p value of 0.000 and the relationship between sex and the incidence of hypertension was 1.384 with a 95% CI: 1.074-1.784. The combined effect also produces a Z-value of 2.510 and a p-value of 0.012.